Increased glucocerebrosidase (GBA) 2 activity in GBA1 deficient mice brains and in Gaucher leucocytes. Issue 5 (15th November 2012) - Burke, Derek G.; Rahim, Ahad A.; Waddington, Simon N.; Karlsson, Stefan; Enquist, Ida; Bhatia, Kailash; Mehta, Atul; Vellodi, Ashok; Heales, Simon
Abstract: Lysosomal glucocerebrosidase (GBA1) deficiency is causative for Gaucher disease. Not all individuals with GBA1 mutations develop neurological involvement raising the possibility that other factors may provide compensatory protection. One factor may be the activity of the non‐lysosomal β‐glucosidase (GBA2) which exhibits catalytic activity towards glucosylceramide and is reported to be highly expressed in brain tissue. Here, we assessed brain GBA2 enzymatic activity in wild type, heterozygote and GBA1 deficient mice. Additionally, we determined activity in leucocytes obtained from 13 patients with Gaucher disease, 10 patients with enzymology consistent with heterozygote status and 19 controls. For wild type animals, GBA2 accounted for over 85 % of total brain GBA activity and was significantly elevated in GBA1 deficient mice when compared to heterozygote and wild types (GBA1 deficient; 92.4 ± 5.6, heterozygote; 71.5 ± 2.4, wild type 76.8 ± 5.1 nmol/h/mg protein). For the patient samples, five Gaucher patients had GBA2 leucocyte activities markedly greater than controls. No difference in GBA2 activity was apparent between the control and carrier groups. Undetectable GBA2 activity was identified in four leucocyte preparations; one in the control group, two in the carrier group and one from the Gaucher disease group. Work is now required to ascertain whether GBA2 activity is a disease modifying factor in Gaucher disease and to identify the mechanism(s) responsible for triggering increased GBA2 activity in GBA1 deficiency states.